PERSPEKTIF TEORI SOSIAL EMILE DURKHEIM DALAM SOSIOLOGI PENDIDIKAN - Arifuddin M. Arif (Program Studi Tadris Ilmu Pengetahuan Sosial (TIPS) IAIN Palu, 2020)
This study is oriented towards Durkheim's theoretical analysis of social theories in the context of the sociology of education. This study aims to reveal the perspective and construction of Durkheim's sociological views of education and its relevance in the current social phenomena of education. With a descriptive analysis approach through literature studies, it is concluded that the dimensions of Durkheim's social theory, with the paradigm of social facts, appear in the elements forming social cohesion or social solidarity, division of labor in society, new social implications that give rise to anomie symptoms, community development and suicide (scuidi ), religion and morality, and collective values. Durkheim recommends that social studies, including the study of education, be carried out according to empirical standards with a major focus on social facts. Durkheim has contributed to the construction of the education system with a sociological approach based on a functional structural approach and a theory of social facts, social solidarity, and morals. Durkheim emphasized educational buildings based on strengthening the values ​​of collective awareness, plus providing knowledge and skills of students to survive in life.